T cell factor-activated transcription is not sufficient to induce anchorage-independent growth of epithelial cells expressing mutant β-catenin - Barth, Angela I. M. (The National Academy of Sciences, 1999)
N-terminal mutations in β-catenin that inhibit β-catenin degradation are found in primary tumors and cancer cell lines, and increased β-catenin/T cell factor (TCF)-activated transcription in these cells has been correlated with cancer formation. However, the role of mutant β-catenin in cell transformation is poorly understood. Here, we compare the ability of different N-terminal mutations of β-catenin (ΔN131, ΔN90, ΔGSK) to induce TCF-activated transcription and anchorage-independent growth in Madin–Darby canine kidney epithelial cells. Expression of ΔN90 or ΔGSK β-catenin increased TCF-activated transcription but did not induce significant anchorage-independent cell growth. In contrast, deletion of the α-catenin-binding site in ΔN131 β-catenin reduced TCF-activated transcription, compared with that induced by ΔN90 or ΔGSK β-catenin, but significantly enhanced anchorage-independent cell growth.